Energy communities in a distributed-energy scenario. Four different kinds of community arrangements. - Moroni, Stefano; Alberti, Valentina; Antoniucci, Valentina; Bisello, Adriano (Springer, 2018)
Distributed-energy generation enables a closer link to be established between energy production and energy consumption, but it does not, in itself, necessarily entail any particular role or organization for groups of people. Nevertheless, because of the distributed-energy spread, the phenomenon of so-called energy communities is growing: all over the world, different kinds of groups organized to produce and consume energy are flourishing. In this regard, the term 'energy community' is used in a generic sense to refer to heterogeneous phenomena. This work contributes to the study of energy communities by identifying key features that enhance understanding of what energy communities are. Since the literature seems to offer only partial points of view, this chapter intends to contribute to building a new taxonomy of energy communities with which to understand the nature and possible effects of the phenomenon. A first distinction can be drawn between place-based communities and non-place-based ones: in the first case, there is coherence between the community and a specific territory; this does not occur in the second case. Another difference is apparent between communities which form and operate only for energy purposes and those which instead add other purposes; in this regard, we can further distinguish between 'energy-only communities' and 'multi-issue communities'. These two pairs of possibilities give rise to a four-cell matrix: that is, to four main cases of energy communities.
Keywords: Energiepolitik; Dezentrale Energieversorgung; Energiebedarf; Energieverbrauch; Klassifikation; Sharing Economy